Night sounds - Sobrino, Javier (Groundwood Books, 2013)
When the moon comes up over the mountains, all the animals in the rain forest go to sleep. But what's that noise? And how can the animals make it stop? Written and illustrated with very young children in mind, this book is perfect for bedtime. Children will be intrigued by the mystery of who is crying in the abandoned box and what he could be crying about, and they will be reassured when the little elephant's mother returns just in time to give him a good night kiss. They will also be delighted by the surprise twist at the end, when a human child begins to cry just when the animals think their troubles are over for the night- and like the little elephant, readers will know exactly what the human child needs.